Cannulated, locking blade plates for proximal femoral osteotomy in children and adolescents. (April 2015) - Zhou, Leena; Camp, Mark; Gahukamble, Abhay; Khot, Abhay; Graham, H. Kerr
Background: Proximal femoral osteotomy is the most common major reconstructive surgery in the region of the hip joint in children and adolescents. Given that it may be required across a wide range of ages and indications, appropriate instrumentation is necessary to ensure a technically satisfactory result. Recent developments in fixation include cannulation of the blade plate and locking screw technology. Methods: We conducted a prospective audit of our first 25 patients who had a unilateral or bilateral proximal femoral osteotomy using a recently available system which combines cannulation and locking plate technology. The principal outcome measures were the radiographic position of the osteotomy at the time of union and surgical adverse events. Results: Forty-five proximal femoral osteotomies were performed in 25 patients, mean age 8 years (range 3–17 years), for a variety of indications, the most common of which was hip subluxation in children with cerebral palsy. All osteotomies were soundly united by 6 weeks in children and by 3 months in adolescents, in the position achieved intra-operatively. There were no revision procedures and the technical goals of surgery were achieved in all patients. There was one adverse event, a low-grade peri-prosthetic infection, diagnosed at the time of implant removal. Conclusions: In this prospective audit of our first 25 patients, the new system performed well across a wide range of ages, body weights and surgical indications. Further comparative studies will be required to determine whether it offers additional advantages over more traditional systems.